Islam : its law and society - Jamila Hussain (Annandale, N.S.W. : Federation Press, 2011)
This book provides an introduction to Islamic law for western readers. It explains the origin and development of the Shariah (Islamic law). It contains updated chapters on the Islamic laws of War and Peace, including juristic opinions on the legality of suicide bombing and the use of modern weapons of mass destruction. It explains the commonalities and the differences in family laws, and the differences in Muslim opinion concerning the status of women. It contains a completely rewritten chapter on Islamic finance and rounds off with a look at Muslim communities in Australia and the way they live their lives.--
Previous ed.: 2004 [i.e. 2003]
Includes bibliographical references and index.
Keywords: Islamic law; Muslims -- Legal status, laws, etc. -- Australia